The Analysis of Social Attitudes Rubric Needs Based on Case-Based Learning (CBL) in Islamic Religious Education Learning - Muslim; Heri Effendi; Pebriyenni; Siti Aisyah; Mochammad Arif Budiman (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This research analyzes the social attitudes rubric needs based on Case-Based Learning (CBL) to objectively assess students’ social attitudes in Islamic Religious Education (PAI) learning. Using a descriptive qualitative approach, the data were gathered by observation, interviews with the lecturers and students, and document study. The research result showed an urgent need for a CBL rubric that contains a measurable indicator of collaboration, empathy, responsibility, and social responsiveness. The Case-Based Learning (CBL) integrity has proven a possibility of assessing the attitude more contextually through a real case study relevant to the students’ lives. In conclusion, this rubric development is important to improve the consistency and objectivity of attitude assessment in Islamic Religious Education. This rubric could be a practical reference for lecturers in evaluating a systematic social attitude, strengthening the internalization of socio-religious values in students.